GAYA BAHASA PERBANDINGAN PADA NOVEL DANDAMAN KADA BAPANCUNG KARYA ALIMAN SYAHRANI (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
ABSTRCTThe results of data analysis using stylistic comparisons it was concluded that: (1) Theliterary style of comparison used in the novel Dandaman Kada Bapancung works AlimanSyahrani is stylistic metaphor, synesthesia, simile, allegory, allusion, hyperbole, kiasmus,personification, sinekdoke, euphemism, perifrasa, and symbolic. (2) The meaning of style in thenovel Dandaman comparison Kada Bapancung Aliman work Syahrani is 1. Meaning ofsynchronous language style (language semantic meaning and cultural significance). 2. Meaningdiachronic style. As in the style of metaphorical language in the following sentence of page 3 inthe novel Dandaman Kada Bapancung works Aliman Syahrani there are sentences floating nut(flowers of the guava tree) the meaning of the quote in italics above including the meaning of thelanguage style of diachronic because originally said floating nut (flower of the tree guava) isindeed the true sense, but over time, the word is growing and does not always refer to the actualmeaning, until finally said floating nut (flowers of the guava tree) growing with new meaningsthat have meaning gray hair that grows on the head of someone.Keywords: Novel, Language Style Comparison, Meaning